Peningkatan Keterampilan Pengelolaan Praktikum IPA Berbantuan Smartphone Menggunakan App Phyphox bagi Kelompok MGMP IPA Kabupaten Batang - Muhamad Taufiq; Murbangun Nuswowati; Arif Widiyatmoko; Ni Luh Tirtasari (Yayasan Keluarga Guru Mandiri, 2023)
Based on the results of an initial survey by the Community Service Team (PKM) via Google form to 188 science teachers who are members of the Science MGMP (Subject Teacher Forum) Batang Regency, there are various obstacles to managing science practicum activities, including in terms of limitations in tools and implementation techniques. In addition, science teachers' knowledge is still inadequate in utilizing smartphones as IT-based media, especially the Phyphox App as an alternative to supporting the implementation of science practicum. The purpose of this PKM activity is to improve skills in managing science practicum through the Phyphox App training for the Batang Regency IPA MGMP Group. Solving the problem in this PKM activity is by organizing training and mentoring through a facilitation-based Action Learning model, which is a process by which groups of people come together regularly, help each other to learn, and share experiences. This model is built from the relationship between reflection and action/ action followed by the mentoring phase. The results of PKM activities have shown an increase in skills in managing science practicums assisted by Smartphones using the Phyphox App as expected.